Statistical methods to detect fraud and errors in clinical trials - Buyse, Marc (Henry Stewart Talks, 2016)
Quality by design, Risk based monitoring, Key risk indicators, Central Statistical Monitoring (CSM), SMART CSM engine, Statistical tests and variables, Types of data issues: Fraud, Tampering, Sloppiness, Errors